Measurement of Pseudomonas aeruginosa phenazine pigments in sputum and assessment of their contribution to sputum sol toxicity for respiratory epithelium. - Wilson, R (1988)
The phenazine pigments pyocyanin and 1-hydroxyphenazine were resolved by high-pressure liquid chromatography from the sputum sol phase from 9 of 13 patients with cystic fibrosis or bronchiectasis colonized by Pseudomonas aeruginosa. The concentrations measured were each sufficient to inhibit ciliary beating in vitro and contributed a significant proportion of sol phase toxicity for respiratory epithelium.